2020
DOI: 10.1167/tvst.9.13.4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Optical Coherence Tomography Angiography Changes Related to Small for Gestational Age Pregnancies

Abstract: To study maternal retinal changes in pregnancies that resulted in a small for gestational age (SGA) infant. Methods: Pregnant women with SGA infants at birth and age-matched pregnant women with appropriate for gestational age (AGA) infants at birth (controls) were enrolled. All subjects underwent spectral domain optical coherent tomography angiography (OCTA) imaging using a 10°× 10°scan pattern centered on the fovea. Vessel density (VD) and vessel length density (VLD) of the superficial capillary plexus (SCP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Due to physiologic differences in hydrostatic pressure, structure and function between the SCP and DCP, it may be plausible that they would be affected in a different way during pregnancy (29,30). Recently, Su and co-authors found that women with small for gestational age infants had increases in selective retinal vascular layers, hypothesizing that these compensatory increases in microcirculation parameters were possibly related to placental insufficiency (20). Since preterm pregnancy is characterized by maternal vascular hypoperfusion, we could assume that a common pathophysiological basis in both cases would account for an apparent increase in vascular density and blood flow (20,26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to physiologic differences in hydrostatic pressure, structure and function between the SCP and DCP, it may be plausible that they would be affected in a different way during pregnancy (29,30). Recently, Su and co-authors found that women with small for gestational age infants had increases in selective retinal vascular layers, hypothesizing that these compensatory increases in microcirculation parameters were possibly related to placental insufficiency (20). Since preterm pregnancy is characterized by maternal vascular hypoperfusion, we could assume that a common pathophysiological basis in both cases would account for an apparent increase in vascular density and blood flow (20,26).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Su and co-authors found that women with small for gestational age infants had increases in selective retinal vascular layers, hypothesizing that these compensatory increases in microcirculation parameters were possibly related to placental insufficiency (20). Since preterm pregnancy is characterized by maternal vascular hypoperfusion, we could assume that a common pathophysiological basis in both cases would account for an apparent increase in vascular density and blood flow (20,26). As previously supported, this mechanism could involve the retinal blood flow autoregulation through the release of vasoactive mediating molecules that lead to capillaries adaptations to alterations in the perfusion pressure and metabolic demands of the tissue (31,32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal imaging allows an accessible way to analyze the vascular network, allowing it to be a time and cost-efficient examination modality [34,35]. The eye itself, with its fragile microvasculature, has been shown to be affected by systemic vascular dysregulation, hence reflecting vascular damage of systemic origin [36][37][38]. Thereby, it stands to reason that changes in retinal vasculature, as mentioned above, can be used as an imaging parameter to detect and observe systemic vascular diseases.…”
Section: Introductionmentioning
confidence: 99%